2013
DOI: 10.3892/or.2013.2884
|View full text |Cite
|
Sign up to set email alerts
|

Expression of early growth response-1 in colorectal cancer and its relation to tumor cell proliferation and apoptosis

Abstract: Early growth response-1 (Egr-1) is implicated in the regulation of cell growth, proliferation, differentiation and apoptosis. Egr-1 is considered tobe either a tumor-suppressor or tumor-promoter, depending on the cell type and environment. The aim of the present study was to evaluate the expression of Egr-1 in colorectal cancer and its correlation with tumor cell proliferation, apoptosis and clinicopathological features. The expression of Egr-1 in colorectal cancer tissues was investigated by reverse transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…Egr1 is expressed at high levels in transformed differentiated cells and functions as a proto-oncogene in certain tumor types. [33][34][35] Consistently, we find high levels of Cdk6 mRNA paralleled by a statistically significant upregulation of Egr1 in transformed BCR-ABL p1851 cells (supplemental Figure 6A). Chromatin immunoprecipitation (ChIP) analysis revealed the presence of CDK6 at the Egr1 promoter at levels comparable to its binding to the p16…”
Section: Cdk6 Directly Regulates Egr1 Expression In Hematopoietic Cellssupporting
confidence: 66%
“…Egr1 is expressed at high levels in transformed differentiated cells and functions as a proto-oncogene in certain tumor types. [33][34][35] Consistently, we find high levels of Cdk6 mRNA paralleled by a statistically significant upregulation of Egr1 in transformed BCR-ABL p1851 cells (supplemental Figure 6A). Chromatin immunoprecipitation (ChIP) analysis revealed the presence of CDK6 at the Egr1 promoter at levels comparable to its binding to the p16…”
Section: Cdk6 Directly Regulates Egr1 Expression In Hematopoietic Cellssupporting
confidence: 66%
“…Loss of Egr-1 expression has been associated with invasion and anti-apoptotic events, whereas overexpression of Egr-1 suppressed the tumorigenicity and metastatic potential in several cancer cells including lung [34,35]. However, opposite role of Egr-1 were also found in several studies [36,37]. Thus Egr-1 is considered to play dual roles depending on the cell types and environment.…”
Section: Discussionmentioning
confidence: 99%
“…However, in metastatic tumors, nuclear EGR1 expression was significantly higher in primary tumors compared with that in paired metastatic lymph node tumors. Previous study showed that, in colorectal cancers, EGR1 protein expression was higher in the cytoplasm of metastatic lymph node tissues when compared to that in non-metastatic lymph node tissues [21]. It has already been shown that the effects of nuclear EGR1 and cytoplasmic EGR1 on cancer progression are incompatible [22].…”
Section: Discussionmentioning
confidence: 99%